Oral health in relation to nutritional status among 10 years old primary school children in Al-Hillah city/ Iraq - Sarah Y. AL Khafaji; Nadia A Al Rawi (College of Dentistry/ University of Baghdad, 2019)
Background: Oral health and nutrition are in interdependent relationship that good nutritional health enhancing good oral health. Nutrition can affect the development and integrity of oral cavity and the progression of oral disease. The aim of the present study was to assess the prevalence of the gingival health condition in relation to the nutritional status, among 10 years old primary school children in urban and rural area in Al-Hillah city. Material and method: Eight hundred ninety one (891) students, aged10 years old, selected randomly from different primary schools, in urban and rural area in Al-Hillah city, were included in this study. Oral examination including of plaque index assessment, which was done according to the criteria by Silness and Loe, in 1964, gingival health conditions was determined according to Loe and Silness, 1963. Nutritional status was assessed using body mass index (BMI), following the criteria of Centers for Disease Control and Prevention growth chart (CDC). Statistical analysis was done using Kruskal Wallis test, Mann-Whitney U test and ANOVA, p-value of < 0.05 was considered as statistically significant. Results: This study showed that the majority of the sample was found to be with normal gingival health condition. No significant difference was observed between the gingival index in relation to gender, or residence also, no significant result was found, between plaque and gingival index in relation to the nutritional status. Conclusion: The majority of the sample with normal gingiva however the nutritional status had no significant effect on gingival health condition while the urbanization had an effect on oral hygiene